A facile co-precipitation synthesis of robust NiFe phosphate electrocatalysts for efficient oxygen evolution in AEMWE - Yu Yu; Jun Liu; Changhao Liang (Applied Catalysis O: Open)
In this study, a straightforward and cost-effective co-precipitation method is employed to synthesize nickel iron phosphate(NiFe Pi) nanomaterials for oxygen evolution reaction (OER) electrocatalysis. The results demonstrate that the OER electrocatalytic activity of these materials are highly sensitive to the ratio of Ni and Fe precursors. When the nickel‑iron ratio is 4.5:1, the amorphous catalyst exhibits an impressively low overpotential of only 178 mV at a current density of 10 mA/cm2 in 1 M KOH solution, with a Tafel slope as low as 47.05 mV/dec, indicating superior recation kinetics. The influence of different Ni/Fe ratios on the performance of NiFe Pi catalysts is also thoroughly discussed. The synthesized NiFe Pi catalysts were further utilized to fabricate membrane electrode assemblies (MEAs) for applications. Single cell testing revealed that the Ni4.5Fe Pi catalyst, with a mass loading of 1.5 mg/cm2 in the MEA, achieved the lowest working potential of 1.81 V at a current density of 1 A/cm2. This outstanding performance highlights its significant potential for commercial applications in the field of electrolysis.